2021
DOI: 10.1172/jci.insight.149346
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial STING controls Tcell transmigration in an IFN-I dependent manner

Abstract: The stimulator of interferon genes 1 protein senses cyclic di-nucleotides released in response to double stranded DNA, and functions as an adaptor molecule for type I interferon (IFNI) signaling by activating IFNI stimulated genes (ISG). We found impaired T cell infiltration into the peritoneum in response to TNFα in global and EC-specific STING-/-mice and discovered that T cell transendothelial migration (TEM) across mouse and human endothelial cells (EC) deficient in STING was strikingly reduced compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The pro-inflammatory cytokine TNF-α, which can be released by pro-inflammatory macrophages, was also similarly increased in the hearts of WT and CD43−/− mice in response to cardiac pressure overload, compared to Sham controls, suggesting that CD43 does not contribute to cardiac TNF-α expression in experimental HF ( Figure 4E ). A characteristic of pro-inflammatory cardiac infiltrating myeloid cells is the production of the chemokine CXCL10, which is a potent chemoattractant for Th1 cells and is mainly secreted by immune cells ( Ngwenyama et al, 2019 ; Anastasiou et al, 2021 ). Given the striking decrease of CD4+ T cells in the CD43−/− TAC hearts, we next investigated cardiac CXCL10 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The pro-inflammatory cytokine TNF-α, which can be released by pro-inflammatory macrophages, was also similarly increased in the hearts of WT and CD43−/− mice in response to cardiac pressure overload, compared to Sham controls, suggesting that CD43 does not contribute to cardiac TNF-α expression in experimental HF ( Figure 4E ). A characteristic of pro-inflammatory cardiac infiltrating myeloid cells is the production of the chemokine CXCL10, which is a potent chemoattractant for Th1 cells and is mainly secreted by immune cells ( Ngwenyama et al, 2019 ; Anastasiou et al, 2021 ). Given the striking decrease of CD4+ T cells in the CD43−/− TAC hearts, we next investigated cardiac CXCL10 expression.…”
Section: Resultsmentioning
confidence: 99%
“…As a representative example, the bronchial circulation (which arises from the aorta and intercostal arteries with high pressure) supplies a small proportion of the pulmonary tissue in mice compared to humans. These differences seem of importance when studying SAVI, where the vascular phenotype is predominant and endothelial cells may be a key player of lung disease [69]. Secondly, STING protein differs between humans and mice [70].…”
Section: Futures Perspectives To Decipher Savi Lung Disease Pathogenesismentioning
confidence: 99%
“…Tumor blood vessels appear disorganized and immature, which reduces chemotaxis of immune cells into TME but increases the distant metastasis of tumor cells. A recent study proposed that T-cell transendothelial migration was regulated by endothelial STING in an IFN-I-dependent manner ( Anastasiou et al, 2021 ). IFN-β was proposed to downregulate VEGF expression and suppress tumor angiogenesis ( Takano et al, 2014 ), but it was also shown that IFN-α and IFN-β promoted vasculogenic mimicry formation and facilitated tumor growth ( Jablonska et al, 2010 ; Yeh et al, 2018 ).…”
Section: Remodeling Of Tme Induced By Dna Damage Through the Cgas/sti...mentioning
confidence: 99%